2020
DOI: 10.1111/oik.07559
|View full text |Cite
|
Sign up to set email alerts
|

Environmental controls on African herbivore responses to landscapes of fear

Abstract: Herbivores balance forage acquisition with the need to avoid predation, often leading to tradeoffs between forgoing resources to avoid areas of high predation risk, or tolerating increased risk in exchange for improved forage. The outcome of these decisions is likely to change with varying resource levels, with herbivores altering their response to predation risk across heterogeneous landscapes. Such contrasting responses will alter the strength of non‐consumptive predation effects, but are poorly understood i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Furthermore, within habitats that span an intermediate woody plant cover range, we found multiple configurations within similar levels of woody plant cover (e.g., D2 and D3, D4 and D5). This likely results from somewhat different use of habitats by the species [ 32 , 46 , 51 ], implying that relatively small changes in woody plant cover may lead to a restructuring of the herbivore community [see 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, within habitats that span an intermediate woody plant cover range, we found multiple configurations within similar levels of woody plant cover (e.g., D2 and D3, D4 and D5). This likely results from somewhat different use of habitats by the species [ 32 , 46 , 51 ], implying that relatively small changes in woody plant cover may lead to a restructuring of the herbivore community [see 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the abundance and habitat associations of the herbivores, we conducted standardized daily driving transects (20 or 40 km per day) during the wet (January–March, n = 33 days) and dry (July–September, n = 47 days) seasons of 2018, following the guidelines of Caro [ 30 ]. Such transects are a common approach to quantifying herbivore habitat use associations [ 8 , 30 32 ]. These transects were conducted from established dirt roads, which run through representative habitats within the study area, as per Caro [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the ‘landscape of fear’ (Laundré et al, 2001) can become a useful framework for understanding multiple‐predator effects across space. However, Davies et al (2021) showed that prey response to predators in the landscape can be highly variable, highlighting the complexities of multi‐predator effects at broader scales. These authors showed that even though prey species tended to adjust their response to predation risk, risk effects were not uniform across landscapes, varying in response to changing resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Due to taxon‐specific differences in biomechanics, habitat use and foraging traits, appropriate functional responses should be chosen according to the organisms of interest (Dunn & Hovel, 2020), or different functional responses can be evaluated to determine the reliance of the model results on this particular feature (Vos et al, 2004). In addition, responses to predators can be strongly contingent on prey density, due to prey risk assessment (Guariento et al, 2015), or resource availability (Davies et al, 2021), which ultimately determines risk costs. Therefore, as an avenue for future research, we suggest treating costs as a function of prey density, or other environmental variables, and using more realistic functional responses that can better predict phenotype prevalence under specific scenarios, especially when the interaction among prey individuals is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Whether vegetation cover lends an advantage to predator or prey may therefore depend on the hunting mode of the predator and defense mechanisms of the prey. Animal behavioral traits, such as ambush versus cursorial predation and running escape versus hiding, influence how risk and reward are perceived in the context of a habitat's vegetation structure (Davies et al 2021).…”
Section: How Vegetation Structure Influences Animal Behaviormentioning
confidence: 99%